Using existing systematic reviews for developing vaccination recommendations: Results of an international expert workshop. Issue 23 (27th May 2021) - Jo, Catherine L.; Burchett, Helen; Bastías, Magdalena; Campbell, Pauline; Gamage, Deepa; Henaff, Louise; Kagina, Benjamin; Lunny, Carole; Marti, Melanie; Muloiwa, Rudzani; Pieper, Dawid; Thomas, James; et al.
Abstract: National immunization technical advisory groups (NITAGs) develop immunization-related recommendations. Systematic reviews are recommended to be used in this process, but conducting them requires significant resources, which many NITAGs lack. Using existing systematic reviews could help address this problem. The Robert Koch Institute and collaborators set up the SYSVAC2 project to facilitate the retrieval of existing systematic reviews and offer guidance on using them. This will include an online registry of systematic reviews relevant to immunization policy and an online course on how to use existing reviews. This report describes an international expert workshop held in December 2019 to develop consensus on methods for using existing reviews and other relevant factors for the registry and course. Members from NITAGs representing different regions of the world presented their experiences of using systematic reviews and reflected on challenges inhibiting use. Three methodologists considered different aspects of using systematic reviews. Interactive sessions followed, where implications for SYSVAC2 were discussed. Participants supported having critical appraisal ratings, plain language summaries, keyword search, and data visualization functions in the registry. They suggested tailoring course content to different audiences and including overviews of reviews as a topic and examples of how NITAGs have used or could use existing reviews. Participants agreed that whether a review is out-of-date should be decided by those using the review rather than registry staff. The registry could help by highlighting the date of literature search or included primary studies. Participants recommended a visualization function to highlight overlap across reviews and guidance on handling challenges to using reviews, ideally, involving a practical element. No consensus was reached on which critical appraisal tool to use for reviews in the registry, but a majority of participants wanted registry staff to perform appraisals. Formative research is planned before the registry and online course are launched in 2020.